Factors predicting organizational commitment among nurses in state hospitals, Malaysia - Lee, Siew Pien; Chitpakdee, Bunpitcha; Ratanawadee, Chontawan (Faculty of Medicine, International Islamic University Malaysia, 2011)
Introduction: With an increase in national nursing shortage, organizational commitment is extremely important for retention of nurses. This predictive study determines the level of organizational commitment and the predictive ability of perceived organizational support, components of job satisfaction, including pay,task requirement, organizational policies, autonomy, interaction and professional status as well as years of experience on organizational commitment. Method: Data were collected from 416 nurses in four state hospitals in Malaysia, using self-administered questionnaires. The hospitals were selected from each region in Peninsular Malaysia and samples were selected by a random sampling method. Questionnaires, including demographic data, Organizational Commitment Questionnaires, Survey of Perceived Organizational Support,and Index Work Satisfaction were distributed by researcher and research assistants. Stepwise multiple regression technique was used to analyze the data. Results: The results discovered that (1) nearly half of the subjects (48.07%) reported high level of organizational commitment. (2) Professional status, autonomy, interaction, task requirement and years of experience could predict the organizational commitment (ß = 0.52, 0.17, p < 0.01); ß= 0.13, 0.11, 0.09, p < 0.05 respectively). Overall, all predictors explained 33% of variability in the organizational commitment among nurses in state hospitals. Conclusions: This study found that nurses in state hospitals were highly committed to their organizations. Results of this study provide information for nurse administrators to consider and maintain these factors in nursing practice to foster a high level of organizational commitment among Malaysian nurses.